Board Gender Diversity, Board Expertise and Financial Performance of Listed Insurance Companies in Nigeria - Abba, Mohammed; Hanga , Bilyaminu Yusuf; Isaiah, Samuel (Kashere Journal of Management Sciences, 2024)
The study examined the impact of board characteristics on the financial performance of insurance companies in Nigeria for the period of ten (10) years covering 2009 to 2018. The population of the study is all the twenty-eight (28) listed insurance companies from where the twenty-five (25) were sampled. For the purpose of this study, data was extracted from the institution’s published annual audit report and CBN’s annual reports for the ten years under review. The study used descriptive statistics, correlation and multiple regressions to analyze the data. Financial performance was measured using return on assets while board characteristics were measured by gender diversity and Directors’ expertise. The results revealed that board characteristics have a positive and significant impact on financial performance. Also gender diversity and directors’ expertise have positive and significant impact on ROA at 1% level of significance of the sampled companies. The study concluded that the financial performance of listed insurance companies in Nigeria is highly dependent on the level of organizations’ gender diversity and director’s expertise. Recommendations made include; the consideration of experience and expert board members to facilitate board characteristics component of listed insurance companies to be adopted to enhance competitiveness as well as improvements in operational efficiency through application of innovative operational strategies